Analysis of composition and abundance of viral communities associated with coral \(Acropora formosa\) - Nhung, Doan Thi; Ngoc, Bui Van (Academia Journal of Biology, 2021)
Coral reefs harbor the extraordinary biodiversity and not only provide livelihoods for coastal communities but also play a crucial role in economic development generally. Unfortunately, they are in decline in Vietnam and around the world because mass coral bleaching events have become more common worldwide. However, little is discovered, about viruses that infect corals and their symbionts. Herein, we present metagenomic analyses of the viral communities in coral mucus associated with healthy and bleached coral Acropora formosa which was collected at Con Dao Island, Vietnam. Interestingly, the number of viral species in bleached specimens are higher than those in healthy status. Viruses similar to those that infect humans and some marine animals also appeared in the coral viral assemblage. The results indicated that the proportion of shared viruses were quite small, and represented extremely abundance. Among the phage identified, vibriophage and cyanophage were only presented in healthy and bleached coral, respectively. Therefore, coral-associated viruses could prospectively infect all constituents of the holobiont - coral, microalgal and microbial. Thus, we expect viruses to be illustrated prominently in the preservation and breakdown of coral health.